2020 XI International Conference on Electrical Power Drive Systems (ICEPDS) 2020
DOI: 10.1109/icepds47235.2020.9249285
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic Challenges for Engineering Education

Abstract: The COVID-19 pandemic has impacted all the spheres human activities. The problems related with the forced self-isolation of people, closed borders between the countries as well as within the states push towards digitalization opening opportunities for bringing new technologies into everyday life. The paper focuses on the resulting dramatic changes in engineering education due to the current classical learning process paradigm shift. The brief overview of the problems is presented. The main challenge is to teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 6 publications
1
10
0
2
Order By: Relevance
“…Although this is a predictable result, it has also been observed that studies have been carried out on critical mathematics education, mathematics curriculum, teaching practices, teacher beliefs, elementary school mathematics and thematic literacy in connection with this keyword. COVID-19, as expected, has implications for many studies from different educational disciplines published during the pandemic period (Daniels, 2020;Rassudov & Korunets, 2020;Rose, 2020). The relevant finding provides clues that there may be outstanding topics in the field of mathematics education during the pandemic period, especially in the transition from face-to-face education to online learning related to curriculum and teaching design.…”
Section: Discussionsupporting
confidence: 53%
“…Although this is a predictable result, it has also been observed that studies have been carried out on critical mathematics education, mathematics curriculum, teaching practices, teacher beliefs, elementary school mathematics and thematic literacy in connection with this keyword. COVID-19, as expected, has implications for many studies from different educational disciplines published during the pandemic period (Daniels, 2020;Rassudov & Korunets, 2020;Rose, 2020). The relevant finding provides clues that there may be outstanding topics in the field of mathematics education during the pandemic period, especially in the transition from face-to-face education to online learning related to curriculum and teaching design.…”
Section: Discussionsupporting
confidence: 53%
“…This article focuses on microprocessor technology and electrical engineering, so the implications of a pandemic for this field will be mentioned. The study [11] states that in the field of electrical engineering, in the first months of the pandemic, communication was performed primarily via e-mail and up to 11% of exercises were not realized. Another 6% used Messenger for communication, 5% web and cloud, 4% social networks and only 2% used simulators.…”
Section: Introductionmentioning
confidence: 99%
“…Authors [22] mentioned that COVID-19 related isolation introduced challenges in engineering education in Moscow, Russia. The authors questioned the legal perspective of distance learning and also questioned the efficiency of distance classes.…”
Section: Globally Observed Covid-19 Challenges On Educationmentioning
confidence: 99%
“…Remote Engineering Education, USA [33] Transitioning to remote learning in a very short time puts challenges to instructors and students. Lab-based courses are a real challenge Lack of face-to-face interaction developed negative emotions and anxiety among students Providing a positive learning experience to students Engineering Education, Moscow, Russia [22] Engineering education is forced to change as fast as ever before.…”
Section: Globally Observed Covid-19 Challenges On Educationmentioning
confidence: 99%